2009
DOI: 10.1080/13668250903074489
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mealtime changes for adults with cerebral palsy and the implications for support services

Abstract: Adults with cerebral palsy may experience gradual changes in their swallowing and mealtime capabilities from as early as 30 years of age. Regular collaborative assessment and involvement of all stakeholders in decisions are important to facilitate compliance with recommendations, ongoing safety, and optimal well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 22 publications
2
47
0
3
Order By: Relevance
“…Difficulties and discomfort during a meal situation have a negative impact on an individual's self-esteem and a negative consequence may be that the meal situation itself becomes associated with discomfort (see e.g. Lance, 2007;Balandin et al, 2009). This lead to unwillingness to use the eating aid, as it may create undignified meal situations.…”
Section: Reflections On the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties and discomfort during a meal situation have a negative impact on an individual's self-esteem and a negative consequence may be that the meal situation itself becomes associated with discomfort (see e.g. Lance, 2007;Balandin et al, 2009). This lead to unwillingness to use the eating aid, as it may create undignified meal situations.…”
Section: Reflections On the Resultsmentioning
confidence: 99%
“…Meal situations, which have a high cultural value in human life, are not always enjoyable situations for everyone (Mintz & Du Bois, 2002). People may experience difficulties and discomfort during meal situations that affect their self-esteem and social relationships (Balandin et al, 2009). People who need the help of others during meal situations can experience low self-esteem and feelings of stigmatization, which can lead to isolation (Martinsen et al, 2008).…”
Section: The Meal Situation and An Eating Aidmentioning
confidence: 99%
“…Although it suggested that dysphagia is slowly progressive 5 , the variability of symptoms emergence was supreme when it was prepared the Speech, Language and Hearing therapeutic process to dysphagia in MJD patients. Moreover, as it was found in studies about other chronic or chronic-degenerative diseases, the QOL evaluation in dysphagia and the actions planning impacted on the functionality committed by the disease, causing promotion of general well-being of people 20,25,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Such dysphagia-related safety incidents are expensive to governments and disability organisations (Access Economics, 2008). Additionally, they are distressing to the person with dysphagia (Balandin, Hemsley, Hanley, & Sheppard, 2009) and those who provide care and support (Ball et al, 2012).…”
Section: Dysphagia-related Safety Incidents and Patient Safety Framewmentioning
confidence: 99%